ZAKAT IN REDUCING STUNTING: A CASE STUDY OF COLLABORATION BETWEEN ZAKAT INSTITUTIONS AND LOCAL GOVERNMENT IN BENGKULU CITY, INDONESIA - Rahmat, Ihsan; Ardita, Rahma; Ramdhani, Rahmat (UIN Sunan Kalijaga, 2025)
The national prevalence of stunting in Indonesia declined from 21.5% in 2023 to 19.8% in 2024, according to the Indonesian Nutritional Status Survey (SSGI). Multisectoral efforts have been continuously undertaken from the national to the local level. This study aims to examine the collaborative mechanism and respective roles of the National Amil Zakat Agency (BAZNAS) and the Office for Women’s Empowerment, Child Protection, Population Control, and Family Planning (DP3AP2KB) in reducing stunting in Bengkulu City. Data were collected through in-depth interviews with 11 informants, analysis of policy documents, cooperation agreements, and financial reports, as well as participatory observation in the Pemberian Makanan Tambahan (PMT). The findings reveal that this collaboration is structured through an annually renewed Memorandum of Understanding (MoU) that delineates role-sharing. BAZNAS focuses on channeling zakat funds and coordinating the distribution of supplementary nutrition, whereas DP3AP2KB provides beneficiary data, family assistance, and monitoring and evaluation. This pattern not only addresses institutional limitations but also illustrates how the synergy of Islamic philanthropy and local government can reinforce sustainable nutrition interventions. It is recommended that this role-sharing model be institutionalized and replicated at the national level to accelerate stunting reduction targets.